Idiopathic Systemic Capillary Leak Syndrome: A Case Report - YARDIMCI, Bulent; Kazancioglu, RÜMEYZA; KAZANCIOĞLU, RÜMEYZA (My University, 2016)
Introduction: Idiopathic systemic capillary leak syndrome (ISCLS) is rarely seen, and presents with recurrent episodes of hypotension, shock, hemoconcentration, and hypoproteinemia. The main pathology is the dysfunction of the vascular endothelium, and it is characterized by an increase of capillary permeability that is accompanied by the loss of intravascular fluid and protein. Case Presentation: We present a 58-year-old female who presented with peripheral edema, leg pain, and syncope at the emergency department. Interestingly demyemilising neuropathy, which is a rare finding, ensued on day 4. She is still being treated using intravenous immunoglobulin therapy. Conclusions: The early signs and symptoms of ISCLS may be subtle; therefore the diagnosis can easily be missed and prompt treatment of the syndrome may be postponed. Thus, the clinician must consider ISCLS in differential diagnosis in cases of hypotension, hemoconcentration, and hypoalbuminemia.